2016
DOI: 10.15296/ijwhr.2016.06
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Effective Factors and its Prevalence on Postpartum Depression Among Women in the City of Qom, Iran

Abstract: IntroductionStudies have shown that women suffer from depression more than men (1). Among different types of depression, postpartum depression is worthy of significant attention because it not only affects mother's health, but also adversely affects growth and psychological evolution of the newborn (2,3). In many women, child birth is a stress-causing factor which is the stimulus for beginning of an acute depression or its recurrence (4). In fact, the period after the childbirth is the transitional period in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In the studies conducted in Iran, postpartum depression has shown a high prevalence. For instance, in research by Sadat et al (9) and Habibzadeh et al (10), the prevalence of this disease was reported as 39% and 27%, respectively. Postpartum depression can be accompanied by a decrease in mothers' activities and disturbance in the relationship between mother, child, and family.…”
Section: Introductionmentioning
confidence: 95%
“…In the studies conducted in Iran, postpartum depression has shown a high prevalence. For instance, in research by Sadat et al (9) and Habibzadeh et al (10), the prevalence of this disease was reported as 39% and 27%, respectively. Postpartum depression can be accompanied by a decrease in mothers' activities and disturbance in the relationship between mother, child, and family.…”
Section: Introductionmentioning
confidence: 95%
“…Analysis of the relationship between the method of delivery and postpartum depression was obtained from 21 literatures that have been reviewed. 13 literatures stated that the delivery method is significantly related to the incidence of postpartum depression (Xie et al, 2011;Smorti et al, 2019;Yokoyama et al, 2021;Nelson et al, 2013;Sylvén et al, 2017;Deng et al, 2014;Taherifad et al, 2013;Al Nasr et al, 2020;Meky et al, 2020;Kim & Dee, 2018;Jadoon et al, 2020;Mathisen et al, 2013;Ariyanti et al, 2016), while eight other literatures state that delivery method is not associated with the incidence of postpartum depression (Alharbi et al, 2014;Suhitaran et al, 2019;Duma et al, 2020;Sadat et al, 2014;Cirik et al, 2016;Kaya et al, 2019;Habibzadeh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Eight literatures reported that delivery method is not associated with postpartum depression (Alharbi et al, 2014;Suhitaran et al, 2019;Eckerdal et al, 2018;Duma et al, 2020;Sadat et al, 2014;Cirik et al, 2016;Kaya et al, 2019;Habibzadeh et al, 2016). This because mode of delivery does not directly affect postpartum depression but there are other psychological factors from the mother such as a history of depression, depression during pregnancy, and a family history of depression that actually has an impact on postpartum depression.…”
Section: Correlation Between Mode Of Delivery and Postpartum Depressionmentioning
confidence: 99%
“…[ 3 ] Studies indicate that PPD has a high prevalence in the Middle East[ 3 ] and its prevalence in Iran has been reported between 7% and over 60%. [ 4 5 ] Women experience this disease mostly with symptoms such as low mood, anorexia, sleep disorder, feeling sad, suicidal thoughts, low sex drive, lack of enjoyment in life, negative thoughts, and guilt. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%